PENCEGAHAN PRAKTIK KEJAHATAN EKONOMI DALAM PERDAGANGAN BEBAS – ORIGIN FRAUD DALAM INDUSTRI MEBEL KAYU DI JEPARA - Utama, Tri Cahya; Windiani, Reni; Hanura, Marten; Puspapertiwi, Sheiffi; H.P, Shary Charlotte; Basith Dir, Andi Akhmad; Putranti, Ika Riswanti; Rosyidin, Mohamad; S, Rr. Hermini; Wahyudi, Fendy E; Paramasatya, Satwika; Farabi, Nadia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Indonesia has been known to have abundant natural resources and culture-based creative industries. The country is therefore vulnerable to the practice of fraud of origin. One of many industrial sectors susceptible to thatparticular crime is the wooden furniture businesses. In many cases, it is apparent that natural products and raw materials of Indonesia are being exported without listing the country as the place of origin. The most commonIndonesian material falls within this illegal practice are timber products. In the province of Central Java, Jepara has been a prominent center of timber industry producing high quality timber products and wooden raw materials.From a unique standpoint, the timber industry in Jepara is deeply rooted to the culture and identity of the natives, making the attempt to separate the discussion between timber industry and the people of Jepara not onlyÂ imprudent but virtually impossible. By looking at the statistic in which Jeparaâ€™s public education level is assessed to be still below the national standard, and as well bearing to the general fact that the timber actors in Jepara are more focused on product sales rather than important technical aspects such as certification of origin, it should be projected that crimes such as fraud of origin could be easily committed in Jepara. This study is using a comparative advantage theory and theories or models of H-O to investigate how the practice of fraud of origin in Jepara occurs and how to resolve such problem.